2008
DOI: 10.1007/s10310-007-0051-7
|View full text |Cite
|
Sign up to set email alerts
|

Line thinning promotes stand growth and understory diversity in Japanese cedar (Cryptomeria japonica D. Don) plantations

Abstract: We studied the effects of line thinning on stand structure, microclimate and understory species diversity of two Cryptomeria japonica D. Don plantations in southcentral Japan. In each of two study sites we compared stand structure between the thinned stand and an adjacent unthinned stand and found that line thinning increased the growth rate of residual trees such that stand basal area may recover within 10 years after thinning. In the thinned stand, more open canopy conditions resulted in higher maximum tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 24 publications
4
27
1
Order By: Relevance
“…Other stand improvement treatments, such as cleaning, thinning and pruning, also exhibited this compatibility, which was in agreement with the findings of Ishii et al (2008). These improvement treatments did not directly affect the tally trees in the stands, or presented a harvest ratio that was similar to (or slightly below) the harvest ratio corresponding to selection cuttings, which suggests that this range of harvest ratios is suitable for achieving effective biodiversity enhancement.…”
Section: Discussionsupporting
confidence: 87%
“…Other stand improvement treatments, such as cleaning, thinning and pruning, also exhibited this compatibility, which was in agreement with the findings of Ishii et al (2008). These improvement treatments did not directly affect the tally trees in the stands, or presented a harvest ratio that was similar to (or slightly below) the harvest ratio corresponding to selection cuttings, which suggests that this range of harvest ratios is suitable for achieving effective biodiversity enhancement.…”
Section: Discussionsupporting
confidence: 87%
“…Line-thinned plots support higher biomass and species richness of understory vegetation and corresponding insect abundance in Cryptomeria plantations in Japan (Maleque et al, 2006b(Maleque et al, , 2007aIshii et al, 2008). Ohsawa (2004) showed that species richness of cerambycid beetles increased in selectively thinned larch plantations (Larix kaempferi) compared to unthinned plantations in Japan.…”
Section: Use Of Bioindicators In Forest Man-agementmentioning
confidence: 90%
“…As a result, studies on the effects of thinning on restoring or rehabilitating plant species diversity are increasing. These studies have shown that thinning enhanced the species richness of broadleaved trees in plantations of Abies sachalinensis [29] and Larix kaempferi [30] in northern Japan, and in C. japonica plantations in western [31] and central [32] Japan. However, Nagai and Yoshida [33] showed that thinning of Picea glehnii plantations in northern Japan reduced plant species diversity because of the direct effect of physical disturbance associated with the activity.…”
Section: Studies On Plant Species Diversity and Species Richness In Pmentioning
confidence: 98%